Multivalued action languages with constraints in CLP(FD) - DOVIER, AGOSTINO; FORMISANO, ANDREA; PONTELLI, ENRICO (Theory and practice of logic programming, 2010)
Action description languages, such as and ℬ (Gelfond and Lifschitz, Electronic Transactions on Artificial Intelligence , 1998, vol. 2, pp. 193—210), are expressive instruments introduced for formalizing planning domains and planning problem instances. The paper starts by proposing a methodology to encode an action language (with conditional effects and static causal laws), a slight variation of ℬ, using Constraint Logic Programming over Finite Domains . The approach is then generalized to raise the use of constraints to the level of the action language itself. A prototype implementation has been developed, and the preliminary results are presented and discussed.